Identification of Potential Prophylactics against Pre-Eclampsia through Magnesium and Zinc Supplementation - Rees, Charles Malcolm (RA Journal of Applied Research, 2018)
Pre-eclampsia is a life-threatening multisystem disorder, affecting approximately 2-3% of all pregnancies and remains a leading cause of perinatal and maternal death.1 Pre-eclampsia is characterised by gestational or pregnancy-induced hypertension in previously normotensive individuals and accompanied with new-onset proteinuria, typically from 20 weeks gestation.2,3 It is described as the ‘disease of theories’ which reflects the considerable amount of uncertainty surrounding its aetiology and pathophysiology. However an abnormal maternal inflammatory response is considered to ensue following placentation.4 Magnesium is a versatile cofactor that plays a pivotal role in blood pressure regulation through its involvement with monitoring vagal tone, reactivity and contractility by activating multiple enzyme pathways. 5,6 Zinc is crucial for normal genetic expression through its involvement with normal protein synthesis and nucleic acid metabolism.7 Deficiencies in either have been implicated with an increased risk of pre-eclampsia.8 This publication offers a potnetial study which would investigate the effects combined Magnesium and Zinc supplementation has with risk of developing pre-eclampsia. It will involve a double blind randomised placebo-controlled trial, with 1204∆ women assigned in equal ratios to either an intervention (n=602) or placebo group (n=602). The intervention group will be given 350mg of Magnesium and 20mg of Zinc, whereas the other group will be given a placebo matched in appearance and taste. Participants will take their tablets once a day orally, from 8-14 weeks gestation until delivery. The participant’s blood pressure and proteinuria levels will be taken initially one week after their trial start date, and every two weeks after that until delivery. The studies primary outcomes are pre-eclampsia, severe hypertension and perinatal mortality. Pre-eclampsia is deﬁned as gestational or pregnancy-induced hypertension (Systolic≥140mmHg or diastolic≥90mmHg) in previously normotensive individuals and accompanied with new-onset proteinuria (≥300mg within 24 hours), typically from 20 weeks gestation. Severe hypertension is defined as a single diastolic blood pressure measurement of ≥120mmHg or two successive measurements of ≥110mmHg with a minimum of 4 hours in between readings. These definitions are taken from the International Society for the Study of Hypertension in Pregnancy (ISSHP). Proteinuria could also be recorded by two measurements of ≥2+ specific gravity via dipstick analysis for Midstream samples of urine (MSSU) or catheter specimens of urine (CSU).